A composite electrolyte and a preparation method thereof, a secondary battery and a preparation method thereof, a battery pack, and an electric device
Patent Information
- Application Number
- CN202611103363.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]本发明的目的之一在于提供一种复合电解质,以解决二次电池无法兼顾热安全性、倍率性能与循环稳定性的问题;目的之二在于提供一种复合电解质的制备方法;目的之三在于提供一种二次电池;目的之四在于提供一种二次电池的制备方法;目的之五在于提供一种电池组;目的之六在于提供一种用电设备
[0036]本发明提供的复合电解质通过中间层的快离子导体与表层的无机电解质协同增效,在赋予其高离子电导率与优异机械强度的同时,利用表层的柔性聚合物基体B改善了界面相容性。得益于此结构设计及无溶剂体系,应用该电解质的二次电池表现出显著提升的循环稳定性、倍率性能及热安全性。
Smart Images

Figure CN122907714A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of electrolyte materials technology, and in particular to a composite electrolyte and its preparation method, a secondary battery and its preparation method, a battery pack, and electrical equipment. Background Technology
[0002] In current liquid rechargeable battery technology, organic electrolytes with added functional components are commonly used to balance high energy density and good cycle stability. However, the organic solvents in these electrolytes are inherently flammable, making the batteries prone to thermal runaway under extreme conditions, posing serious safety hazards such as fire and even explosion. Because there is an irreconcilable contradiction between improving energy density and ensuring intrinsic safety in liquid electrolyte systems, they are no longer sufficient to meet the development requirements of next-generation high-safety, high-energy-density batteries.
[0003] Solid electrolytes, especially polymer electrolytes, are considered potential alternatives due to their superior safety and non-flow properties compared to liquid electrolytes. However, existing polymer electrolytes generally face the technical bottleneck of low ionic conductivity, which fails to meet the basic requirements for room temperature applications. Furthermore, most polymer electrolytes suffer from insufficient mechanical strength, further limiting their practical applications.
[0004] Therefore, there is an urgent need to develop a new type of composite electrolyte material in order to simultaneously improve the rate performance and cycle stability of secondary batteries while ensuring their thermal safety. Summary of the Invention
[0005] One objective of this invention is to provide a composite electrolyte to solve the problem that secondary batteries cannot simultaneously achieve thermal safety, rate performance, and cycle stability; a second objective is to provide a method for preparing the composite electrolyte; a third objective is to provide a secondary battery; a fourth objective is to provide a method for preparing a secondary battery; a fifth objective is to provide a battery pack; and a sixth objective is to provide an electrical device.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] A composite electrolyte includes a first surface layer, an intermediate layer, and a second surface layer stacked sequentially. The intermediate layer includes a polymer matrix A, a fast ion conductor, and a lithium salt A. The first surface layer and the second surface layer each independently include a polymer matrix B, an inorganic electrolyte, and a lithium salt B.
[0008] Based on the aforementioned technical methods, multi-performance synergistic optimization of composite electrolytes is achieved through layered functional design, thereby improving the thermal safety, rate performance, and cycle stability of secondary batteries. Specifically, the intermediate layer significantly enhances ionic conductivity through the introduction of fast ion conductors, while the first and second surface layers employ organic-inorganic composite electrolytes. The introduction of inorganic solid electrolytes enhances mechanical strength, and the polymer matrix buffers electrode deformation.
[0009] Furthermore, the polymer matrix A and the polymer matrix B each independently include at least one of poly(meth)acrylic acid, poly(meth)acrylate, polycarbonate, polyacetate, polyolefin, and polyether-modified (meth)acrylate.
[0010] Based on the above technical means, polymer matrix A and polymer matrix B are selected from the above polymers, further reducing the crystallinity of the polymer matrix itself and increasing the active ion mobility, thereby improving the rate performance of the secondary battery.
[0011] Further, the poly(meth)acrylic acid includes at least one of polyacrylic acid and polymethacrylic acid; and / or, the poly(meth)acrylate includes at least one of polyacrylate, polymethyl methacrylate, polyethyl methacrylate, and polydiacrylate; and / or, the polycarbonate includes at least one of polypropylene carbonate, polyvinyl carbonate, and polyvinyl carbonate; and / or, the polyacetate includes polyvinyl acetate; and / or, the polyolefin includes polystyrene; and / or, the polyether-modified (meth)acrylate includes at least one of polyethylene glycol dimethacrylate, polyethylene glycol methacrylate, polyethylene glycol methyl ether methacrylate, and polyethylene glycol dimethyl ether.
[0012] Based on the above-mentioned technical means, the polymers of the above-mentioned sub-types further optimize the comprehensive performance of the polymer matrix, which is more conducive to improving the function of the composite electrolyte, and thus better synergistically improves the cycle performance, rate performance and energy density of the secondary battery.
[0013] The ratio of the thickness of the first surface layer to the thickness of the intermediate layer is (1-3):(10-30); and / or, the ratio of the thickness of the second surface layer to the thickness of the intermediate layer is (1-3):(10-30).
[0014] Based on the above technical means, the synergistic adaptation of the functions of each layer can be achieved, further improving the overall performance of the composite electrolyte, which is more conducive to improving the cycle performance and rate performance of the secondary battery.
[0015] Furthermore, the thickness of the intermediate layer is 100-300 μm; and / or, the thickness of the first surface layer is 10-30 μm; and / or, the thickness of the second surface layer is 10-30 μm.
[0016] Based on the above technical means, the synergistic adaptation of the functions of each layer can be achieved, further improving the overall performance of the composite electrolyte, which is more conducive to improving the cycle performance and rate performance of the secondary battery.
[0017] Further, in the first surface layer, the mass ratio of the polymer matrix B, the inorganic electrolyte, and the lithium salt B is (50-100):(10-50):(10-60); and / or, in the intermediate layer, the mass ratio of the polymer matrix A, the fast ion conductor, and the lithium salt A is (30-70):(30-70):(10-60); and / or, in the second surface layer, the mass ratio of the polymer matrix B, the inorganic electrolyte, and the lithium salt B is (50-100):(10-50):(10-60).
[0018] Based on the above technical means, the components can fully exert their synergistic effect, further optimize the various properties of the composite electrolyte, and are more conducive to improving the cycle performance and rate performance of the secondary battery.
[0019] Furthermore, the inorganic electrolyte includes at least one of lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium lanthanum zirconium tantalum oxide, lithium titanium aluminum phosphate, and lithium aluminum germanium phosphate; and / or, lithium salt A and lithium salt B each independently include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium difluorooxalate borate; and / or, the fast ion conductor includes at least one of ionic liquid and succinate.
[0020] Based on the above technical means, the performance of composite electrolytes can be further optimized, which is more conducive to improving the cycle performance and rate performance of secondary batteries.
[0021] A second aspect of this invention provides a method for preparing a composite electrolyte, comprising the following steps:
[0022] 1) A first mixture comprising monomers of polymer matrix A, fast ion conductor, lithium salt A, crosslinking agent A and initiator A is subjected to a first polymerization reaction to obtain an intermediate layer;
[0023] 2) A second mixture comprising a monomer of polymer matrix B, an inorganic electrolyte, lithium salt B, a crosslinking agent B, and an initiator B is coated onto the first and second surfaces of the intermediate layer, respectively, and a second polymerization reaction is carried out to obtain the composite electrolyte; the first and second surfaces are arranged opposite to each other.
[0024] Based on the above technical means, the composite electrolyte has achieved a synergistic improvement in ionic conductivity, mechanical strength, flame retardancy and interface stability, ultimately improving the cycle performance and rate performance of the secondary battery.
[0025] Furthermore, the conditions for the first polymerization reaction are ultraviolet irradiation for 0.5-2 hours or heating at 50-70°C for 1-4 hours; and / or, the conditions for the second polymerization reaction are ultraviolet irradiation for 0.5-2 hours or heating at 50-70°C for 1-4 hours.
[0026] Based on the above technical means, the preparation quality and performance stability of composite electrolytes can be further guaranteed, which is more conducive to giving full play to the synergistic effect of each component, and thus better improving the cycle performance and rate performance of secondary batteries.
[0027] A third aspect of the present invention provides a secondary battery comprising the composite electrolyte described above, or a composite electrolyte prepared by the preparation method described above.
[0028] A fourth aspect of the present invention provides a method for preparing a secondary battery, comprising the following steps:
[0029] A positive electrode and a negative electrode are respectively disposed on both sides of the composite electrolyte to obtain the secondary battery; or,
[0030] A first polymerization reaction is carried out on a first mixture comprising a monomer of polymer matrix A, a fast ion conductor, lithium salt A, and initiator A to obtain an intermediate layer;
[0031] A second mixture comprising a monomer of polymer matrix B, an inorganic electrolyte, lithium salt B, and initiator B is coated onto the first and second surfaces of the intermediate layer, respectively. Subsequently, a positive electrode is disposed on the side of the second mixture away from the first surface, and a negative electrode is disposed on the side of the second mixture away from the second surface. A second polymerization reaction is carried out to obtain the secondary battery. The first and second surfaces are arranged opposite to each other.
[0032] Based on the above-mentioned technical means, the secondary battery has excellent thermal safety, cycle performance and rate performance due to the use of the above-mentioned composite electrolyte.
[0033] The fifth aspect of the present invention provides a battery pack comprising the secondary battery described above, or a secondary battery prepared by the preparation method described above.
[0034] A sixth aspect of the present invention provides an electrical device comprising the battery pack described above.
[0035] The beneficial effects of this invention are:
[0036] The composite electrolyte provided by this invention achieves synergistic effects through the fast ion conductor in the intermediate layer and the inorganic electrolyte in the surface layer. This imparts high ionic conductivity and excellent mechanical strength while improving interfacial compatibility using the flexible polymer matrix B in the surface layer. Thanks to this structural design and solvent-free system, secondary batteries using this electrolyte exhibit significantly improved cycle stability, rate performance, and thermal safety.
[0037] Furthermore, this invention selects poly(meth)acrylic acid, poly(meth)acrylate, polycarbonate, polyacetate, polyolefin, and polyether-modified (meth)acrylate as polymer matrix A and / or polymer matrix B. These polymer matrices have lower crystallinity, which promotes the migration of active ions in the secondary battery and significantly improves the rate performance of the secondary battery. When the ratio of the thickness of the surface layer (first surface layer and second surface layer) to the thickness of the intermediate layer is (1-3):(10-30), the thickness of the intermediate layer is 100-300 μm, and the thickness of the surface layer is 10-30 μm, it can better balance the ionic conductivity of the inorganic electrolyte with the flexibility and mechanical strength of the surface layer. A continuous lithium-ion transport channel is built based on the sufficiently thick intermediate layer, while simultaneously utilizing… A thinner surface layer shortens the ion transport distance in the electrolyte, simultaneously optimizing the cycle performance and rate performance of the secondary battery. When the mass ratio of polymer matrix B, inorganic electrolyte, and lithium salt B in the surface layer is (50-100):(10-50):(10-60), and the mass ratio of polymer matrix A, fast ion conductor, and lithium salt A in the intermediate layer is (30-70):(30-70):(10-60), the components can be better matched. This maintains a stable three-dimensional cross-linked network structure that binds the fast ion conductor, while also increasing the ion carrier concentration and improving ion conduction efficiency. This ensures smoother ion transport within the composite electrolyte and between the composite electrolyte and the electrode, further enhancing the rate performance and cycle performance of the secondary battery. Attached Figure Description
[0038] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0039] Figure 1 This is a cross-sectional SEM image of the composite electrolyte provided in Embodiment 1 of the present invention;
[0040] Figure 2 This is an electrochemical window test diagram of the composite electrolyte provided in Example 1 of the present invention;
[0041] Figure 3The Li∣Li symmetric cells prepared for Examples 1, 3, and Comparative Example 1 of this invention operate at 0.1 mA / cm². 2 A comparison of the results of cyclic tests of charging and discharging for 1 hour each at the current density;
[0042] Figure 4 A comparison of the results of the 0.5C charge-discharge cycle test at 25°C between the Li∣lithium iron phosphate battery assembled with the composite electrolyte provided in Example 1 of the present invention and the Li∣lithium iron phosphate liquid battery assembled with the ether-based liquid electrolyte in Comparative Example 2.
[0043] Figure 5 This is a comparison chart showing the 1C charge-discharge cycle test results of the Li∣lithium iron phosphate batteries prepared in Example 1 and Comparative Example 3 of the present invention at 25°C.
[0044] Figure label:
[0045] 1-First surface layer; 2-Second surface layer; 3-Intermediate layer. Detailed Implementation
[0046] The embodiments of the present invention will be described below with reference to the accompanying drawings and preferred embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are only for illustrating the present invention and not for limiting the scope of protection of the present invention.
[0047] It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. Therefore, the drawings only show the components related to the present invention and are not drawn according to the actual number, shape and size of the components in the actual implementation. In the actual implementation, the form, quantity and proportion of each component can be arbitrarily changed, and the layout of the components may also be more complex.
[0048] To simultaneously improve the thermal safety, rate performance, and cycle stability of rechargeable batteries, the inventors researched existing rechargeable batteries and discovered that the reason existing batteries cannot simultaneously improve these performances is that: existing technologies combine cross-linked polymers with liquid electrolytes to form a gel electrolyte layer, which is then combined with an inorganic solid electrolyte to form a sandwich structure. For example, the middle layer uses cross-linked acrylate to lock in the electrolyte and improve ionic conductivity, while the surface layer is a gel electrolyte to reduce interfacial impedance. Although this approach improves the active ion transport rate through the presence of liquid components and improves interfacial compatibility through the gel layer, it still has the following drawbacks: the gel layer is susceptible to deformation under external forces, leading to electrolyte structural failure and affecting battery cycle stability; the gel layer still contains organic solvents, posing a risk of thermal runaway and leakage.
[0049] Based on this, the first aspect of the present invention provides a composite electrolyte comprising a first surface layer 1, an intermediate layer 3, and a second surface layer 2 stacked sequentially, wherein the intermediate layer 3 comprises a polymer matrix A, a fast ion conductor, and a lithium salt A, and the first surface layer 1 and the second surface layer 2 each independently comprise a polymer matrix B, an inorganic electrolyte, and a lithium salt B.
[0050] It should be noted that both polymer matrix A and polymer matrix B in this invention have a three-dimensional cross-linked network structure. The room temperature conductivity of the fast ion conductor is greater than 10. -4 S / cm. The first surface layer, the intermediate layer and the second surface layer are stacked sequentially in this invention, giving the composite electrolyte a "sandwich structure".
[0051] The composite electrolyte provided by this invention exhibits excellent thermal safety, ionic conductivity, mechanical strength, and interfacial compatibility with the electrode, significantly improving the thermal safety, cycle performance, and rate performance of secondary batteries. This is due to two main reasons: First, by introducing a polymer matrix A and a fast ion conductor into the intermediate layer of the composite electrolyte, the three-dimensional cross-linked network structure of the polymer matrix A uniformly fixes the fast ion conductor within it, maintaining ion penetration pathways while endowing the composite electrolyte with good self-supporting properties. The introduction of the fast ion conductor significantly improves the ionic conductivity of the intermediate layer. Second, by employing an organic-inorganic electrolyte (i.e., a composite of polymer matrix B and inorganic electrolyte) in the first and second surface layers of the composite electrolyte, the introduction of the inorganic electrolyte enhances the mechanical strength of the composite electrolyte and further improves its ionic conductivity. The polymer matrix B effectively buffers the volume deformation of the electrode during charging and discharging, thereby improving the interfacial compatibility between the composite electrolyte and the electrode. Furthermore, the composite electrolyte does not contain organic solvents, fundamentally eliminating the safety hazards they pose and further enhancing the thermal safety of the secondary battery. In summary, through the structural design and material selection of the above-mentioned layers, this invention fully leverages the synergistic effect between the components, thereby improving ionic conductivity, optimizing interface stability, ensuring the thermal safety of the battery, and ultimately synergistically enhancing the cycle performance and rate performance of the secondary battery.
[0052] In one specific embodiment, polymer matrix A and polymer matrix B each independently include at least one selected from poly(meth)acrylic acid, poly(meth)acrylate, polycarbonate, polyacetate, polyolefin, and polyether-modified (meth)acrylate. By selecting the aforementioned polymers for polymer matrix A and polymer matrix B, the crystallinity of the polymer matrix itself is further reduced, and the active ion mobility is increased, thereby improving the rate performance of the secondary battery.
[0053] Preferably, the polymer matrix B includes poly(meth)acrylic acid, poly(meth)acrylate, polycarbonate, and polyacetate. The monomers of these polymers have a permeation effect, which can reduce the thickness of the first and second surface layers, thereby reducing the overall thickness of the composite electrolyte and improving the energy density and rate performance of the secondary battery. This is because a reduced composite electrolyte thickness further shortens the ion conduction distance, improves ion conduction efficiency, and facilitates rapid ion transport between the electrodes and the electrolyte, thus better utilizing the rate output capability of the secondary battery. Simultaneously, the reduced composite electrolyte thickness allows for the inclusion of more electrode active materials within the limited battery space, further increasing the battery's energy density. This synergistic effect with the aforementioned improvements in cycle performance and rate performance further optimizes the overall performance of the secondary battery.
[0054] When the polymer matrix A consists of two or more of the aforementioned specific compounds, the present invention does not impose specific limitations on the proportions between the various specific compounds.
[0055] When the polymer matrix B is two or more of the above-mentioned specific compounds, the present invention does not specifically limit the proportion between the various specific compounds.
[0056] In one specific embodiment, the poly(meth)acrylic acid includes at least one of polyacrylic acid and polymethacrylic acid. These substances possess good lithium affinity and flexibility, which can further enhance the interfacial compatibility between the composite electrolyte and the electrode, better buffer the volume deformation of the electrode during charging and discharging, and simultaneously, the polar groups in their molecular structure can promote the dissociation of lithium salts, further improving the ionic conductivity of the composite electrolyte, thereby enhancing the rate performance and cycle performance of the secondary battery.
[0057] In one specific embodiment, the poly(meth)acrylate includes at least one selected from polyacrylate, polymethyl methacrylate, polyethyl methacrylate, and polydiacrylate. These substances combine flexibility and mechanical strength, enabling them to complement the formability and self-supporting capabilities of the electrolyte while further optimizing interfacial contact and reducing ion transport resistance. Simultaneously, their good compatibility prevents adverse reactions with inorganic electrolytes and lithium salts, thereby improving the rate performance and cycle performance of the secondary battery.
[0058] In one specific embodiment, the polycarbonate includes at least one of polypropylene carbonate, polyethylene carbonate, and polyvinyl carbonate. These substances possess excellent ion conductivity and thermal stability, which can further improve the ion conductivity and thermal safety of the composite electrolyte. Simultaneously, their flexible structure can better adapt to electrode volume deformation and improve interfacial compatibility, thereby enhancing the thermal safety, rate performance, and cycle performance of the secondary battery.
[0059] In one specific embodiment, the polyacetate includes polyvinyl acetate. Polyvinyl acetate has good film-forming properties and flexibility, enhancing the overall mechanical stability of the composite electrolyte. Simultaneously, its polar structure promotes ion transport, further optimizing ion conduction efficiency, thereby improving the rate performance and cycle performance of the secondary battery.
[0060] In one specific embodiment, the polyolefin includes polystyrene. Polystyrene possesses good mechanical strength and chemical stability, further enhancing the structural stability of the composite electrolyte, thereby improving the cycle stability of the secondary battery.
[0061] In one specific embodiment, the polyether-modified (meth)acrylate includes at least one of polyethylene glycol dimethacrylate, polyethylene glycol methacrylate, polyethylene glycol methyl ether methacrylate, and polyethylene glycol dimethyl ether. These substances combine the high ionic conductivity of polyethers with the good moldability of (meth)acrylates, further shortening the ion conduction distance and improving ion conduction efficiency. Simultaneously, their flexible structure better buffers electrode volume deformation, further improving interfacial compatibility and facilitating smooth ion transport between the composite electrolyte and the electrode, thereby enhancing the rate performance and cycle performance of the secondary battery.
[0062] To further improve the rate performance and energy density of secondary batteries, the ratio of the thickness of the first surface layer to the thickness of the intermediate layer, and the ratio of the thickness of the second surface layer to the thickness of the intermediate layer can also be controlled.
[0063] In one specific embodiment, the thickness ratio of the first surface layer 1 to the thickness of the intermediate layer 3 is (1-3):(10-30). Within this range, the thickness ratio of the first surface layer to the intermediate layer can balance the ionic conductivity of the composite electrolyte, the flexibility of the surface layers (first surface layer and second surface layer), and the mechanical strength, which is more conducive to synergistically improving the cycle performance and rate performance of the secondary battery.
[0064] For example, the ratio of the thickness of the first surface layer to the thickness of the intermediate layer is 1:10, 1:20, 1:30, 2:10, 2:20, 2:30, 3:10, 3:20 or 3:30, or a range of any two of these values.
[0065] In one specific embodiment, the ratio of the thickness of the second surface layer 2 to the thickness of the intermediate layer 3 is (1-3):(10-30). Within this range, the ratio of the thickness of the second surface layer to the thickness of the intermediate layer can balance the ionic conductivity of the composite electrolyte, the flexibility of the surface layers (first and second surface layers), and the mechanical strength, which is more conducive to synergistically improving the cycle performance and rate performance of the secondary battery.
[0066] For example, the ratio of the thickness of the second surface layer to the thickness of the intermediate layer is 1:10, 1:20, 1:30, 2:10, 2:20, 2:30, 3:10, 3:20 or 3:30, or a range of any two of these values.
[0067] In one specific embodiment, the thickness of the intermediate layer 3 is 100-300 μm. As the core region for ion conduction, this thickness range provides sufficient space for the three-dimensional cross-linked network structure of the polymer matrix A, which can more uniformly fix the fast ion conductor, ensure the smoothness of the ion permeation pathway, and at the same time give the composite electrolyte better self-supporting properties, which is more conducive to improving the rate performance of the secondary battery.
[0068] For example, the thickness of the intermediate layer is 100μm, 120μm, 140μm, 160μm, 180μm, 200μm, 220μm, 240μm, 260μm, 280μm or 300μm, or a range of any two of these values.
[0069] In one specific embodiment, the thickness of the first surface layer 1 is 10-30 μm.
[0070] For example, the thickness of the first surface layer is 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm or 30 μm, or a range of any two of these values.
[0071] In one specific embodiment, the thickness of the second surface layer 2 is 10-30 μm.
[0072] For example, the thickness of the second surface layer is 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm or 30 μm, or a range of any two of these values.
[0073] The thicknesses of the first and second surface layers are within the aforementioned range, forming a more reasonable ratio with the intermediate layer. This approach fully leverages the advantages of the organic-inorganic electrolyte (the inorganic electrolyte can further enhance the mechanical strength and ionic conductivity of the composite electrolyte, while the flexibility of the polymer matrix B can better buffer the volume deformation during electrode charging and discharging, improving interfacial compatibility), while also addressing the shortcomings of the composite electrolyte in terms of ion conduction efficiency, mechanical strength, and interfacial compatibility with the electrode.
[0074] In one specific embodiment, the mass ratio of polymer matrix B, inorganic electrolyte, and lithium salt B in the first surface layer 1 is (50-100):(10-50):(10-60). Within this mass ratio range, polymer matrix B provides good flexibility and formability for the first surface layer, better buffering electrode volume deformation and improving interfacial compatibility; inorganic electrolyte further enhances the mechanical strength and ionic conductivity of the first surface layer; lithium salt B provides sufficient charge carriers for ion conduction, further improving the ionic conductivity of the first surface layer, ensuring smooth ion transport between the surface layer and the electrode. The components fully exert their synergistic effect, further optimizing the various performance characteristics of the composite electrolyte, and is more conducive to improving the cycle performance and rate performance of the secondary battery.
[0075] For example, in the first surface layer 1, the mass ratio of polymer matrix B, inorganic electrolyte and lithium salt B is 50:10:10, 50:20:30, 50:50:60, 80:10:10, 80:20:30, 80:50:60, 100:10:10, 100:30:10, 100:50:10, 100:30:30, 100:30:60, 100:10:60, 100:50:60, 100:20:10, 100:50:20 or 100:30:28.7, or a range consisting of any two of these values.
[0076] In one specific embodiment, the mass ratio of polymer matrix A, fast ion conductor, and lithium salt A in the intermediate layer 3 is (30-70):(30-70):(10-60). Within this mass ratio range, polymer matrix A can form a stable three-dimensional cross-linked network structure, more uniformly fixing the fast ion conductor. This ensures the integrity of the ion permeation pathway and endows the composite electrolyte with good self-supporting properties. The high proportion of fast ion conductor can significantly improve the ionic conductivity of the intermediate layer. The synergistic effect of lithium salt A and fast ion conductor further increases the ion carrier concentration and improves ion conduction efficiency. All components fully exert their synergistic effect, further optimizing the various performance characteristics of the composite electrolyte, which is more conducive to improving the cycle performance and rate performance of the secondary battery.
[0077] For example, in the intermediate layer 3, the mass ratio of polymer matrix A, fast ion conductor, and lithium salt A is 30:70:10, 40:60:10, 50:50:10, 60:40:10, 70:30:10, 30:70:60, 40:60:60, 50:50:60, 60:40:60, 50:50:40, or 70:30:60, or a range consisting of any two of these values.
[0078] In one specific embodiment, the mass ratio of polymer matrix B, inorganic electrolyte, and lithium salt B in the second surface layer 2 is (50-100):(10-50):(10-60). Within this mass ratio range, polymer matrix B provides good flexibility and formability for the second surface layer, better buffering electrode volume deformation and improving interfacial compatibility; inorganic electrolyte further enhances the mechanical strength and ionic conductivity of the second surface layer; lithium salt B provides sufficient charge carriers for ion conduction, further improving the ionic conductivity of the second surface layer, ensuring smooth ion transport between the surface layer and the electrode. Each component can fully exert its synergistic effect, further optimizing the various performance characteristics of the composite electrolyte, and is more conducive to improving the cycle performance and rate performance of the secondary battery.
[0079] For example, in the second surface layer 2, the mass ratio of polymer matrix B, inorganic electrolyte and lithium salt B is 50:10:10, 50:20:30, 50:50:60, 80:10:10, 80:20:30, 80:50:60, 100:10:10, 100:30:10, 100:50:10, 100:30:30, 100:30:60, 100:10:60, 100:50:60, 100:20:10, 100:50:20 or 100:30:28.7, or a range consisting of any two of these values.
[0080] In one specific embodiment, the inorganic electrolyte includes at least one of lithium lanthanum zirconium oxide (LLZO), lithium lanthanum titanium oxide (LLTO), lithium lanthanum zirconium tantalum oxide (LLZTO), lithium titanium aluminum phosphate (LATP), and lithium aluminum germanium phosphate (LAGP). All of the above inorganic electrolytes possess excellent ionic conductivity and mechanical strength, which can better enhance the mechanical stability and ionic conductivity of the composite electrolyte. Simultaneously, they exhibit good compatibility with polymer matrix B and lithium salt B, further improving the overall performance of the first and second surface layers, thereby enhancing the cycle performance and rate performance of the secondary battery.
[0081] In one specific embodiment, lithium salt A and lithium salt B each independently include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium difluorooxalateborate. These substances possess high ion dissociation and good ion conductivity, providing sufficient ion carriers for the composite electrolyte, further enhancing ion conductivity. Furthermore, they exhibit excellent compatibility with polymer matrices, fast ion conductors, and inorganic electrolytes, ensuring the structural stability of the composite electrolyte and further improving the cycle performance and rate performance of the secondary battery.
[0082] In this invention, lithium salt A and lithium salt B can be the same or different.
[0083] In one specific embodiment, the fast ion conductor includes at least one of an ionic liquid and succinic anion. The ionic liquid and succinic anion possess high ionic conductivity and good thermal stability, and can synergistically interact with the polymer matrix A and lithium salt A to further improve the ion conduction efficiency of the intermediate layer, while simultaneously enhancing the thermal safety of the composite electrolyte, thereby further improving the thermal safety and rate performance of the secondary battery.
[0084] This invention does not specifically limit the type of ionic liquid, and it can be 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (EMIMTFSI), 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (BMIMTFSI), 1-ethyl-3-methylimidazolium hexafluorophosphate (EMIMPF6), 1-n-butyl-1-methylpyrrolidine di(trifluoromethanesulfonyl)imide (Pyr 14 At least one of FSI).
[0085] A second aspect of this invention provides a method for preparing a composite electrolyte, comprising the following steps:
[0086] 1) A first mixture comprising monomers of polymer matrix A, fast ion conductor, lithium salt A, crosslinking agent A and initiator A is subjected to a first polymerization reaction to obtain an intermediate layer;
[0087] 2) A second mixture comprising a monomer of polymer matrix B, an inorganic electrolyte, lithium salt B, a crosslinking agent B, and an initiator B is coated onto the first and second surfaces of the intermediate layer, respectively, and a second polymerization reaction is carried out to obtain a composite electrolyte; the first and second surfaces are arranged opposite to each other.
[0088] The preparation method provided by this invention significantly improves ionic conductivity by introducing a fast ion conductor in the intermediate layer and forms a stable three-dimensional network structure through a first polymerization reaction, ensuring the uniformity and self-supporting properties of the composite electrolyte. Introducing inorganic electrolytes into the first and second surface layers enhances mechanical strength and ionic conductivity, while utilizing the polymer matrix B to buffer electrode deformation and improve the interfacial compatibility between the composite electrolyte and the electrode. Through the synergistic design of the intermediate and surface layers, a synergistic improvement in ionic conductivity, mechanical strength, flame retardancy, and interfacial stability of the composite electrolyte is achieved, ultimately improving the thermal safety, cycle performance, and rate performance of the secondary battery.
[0089] The present invention does not specifically limit the types of monomers in polymer matrix A and polymer matrix B. For example, the monomers of polymer matrix A include, but are not limited to, at least one of acrylic acid, acrylate, and vinyl acetate, and the monomers of polymer matrix B include, but are not limited to, one of acrylic acid, acrylate, and vinyl acetate.
[0090] This invention does not specifically limit the types of initiator A and initiator B; commonly used initiators in the art can be used. For example, initiator A can be at least one of azobisisobutyronitrile, benzoyl peroxide, tert-butyl peroxide, dimethyl azobisisobutyrate, and their derivatives; initiator B can be at least one of azobisisobutyronitrile, benzoyl peroxide, tert-butyl peroxide, dimethyl azobisisobutyrate, and their derivatives.
[0091] In order to construct a three-dimensional polymer crosslinking network and improve the dimensional stability of the electrolyte, crosslinking agent A and crosslinking agent B are added during the preparation of the intermediate layer.
[0092] The present invention does not specifically limit the types of crosslinking agent A and crosslinking agent B. Crosslinking agent A and crosslinking agent B are each independently selected from at least one of polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and trimethylolpropane triacrylate.
[0093] The present invention does not specifically limit the amount of crosslinking agent A added. In one embodiment, the amount of crosslinking agent A added is 1-2% of the monomer mass of polymer matrix A.
[0094] The present invention does not specifically limit the amount of crosslinking agent B added. In one embodiment, the amount of crosslinking agent B added is 1-2% of the monomer mass of polymer matrix B.
[0095] In this invention, the mass ratio of the monomer of polymer matrix A, fast ion conductor, lithium salt A and initiator A in the first mixture is not specifically limited, as long as the intermediate layer can be obtained.
[0096] In one embodiment, the mass ratio of the monomer of polymer matrix A, fast ion conductor, lithium salt A and initiator A in the first mixture is (30-70):(30-70):(10-60):(0.4-5).
[0097] In this invention, the mass ratio of monomers, fast ion conductors, lithium salt A and initiator A in the second mixture is not specifically limited, as long as an intermediate layer can be obtained.
[0098] In one embodiment, the mass ratio of the monomer of polymer matrix B, inorganic electrolyte, lithium salt B and initiator B in the second mixture is (50-100):(10-50):(10-60):(0.5-5).
[0099] To further improve the uniformity of the intermediate layer, the first surface layer, and the second surface layer, the conditions of the first polymerization reaction and the second polymerization reaction are controlled.
[0100] In one specific embodiment, the conditions for the first polymerization reaction are ultraviolet irradiation for 0.5-2 hours or heating at 50-70°C for 1-4 hours. These limited polymerization reaction conditions further ensure the preparation quality and performance stability of the composite electrolyte, and are more conducive to fully leveraging the synergistic effect of each component, thereby better improving the cycle performance and rate performance of the secondary battery. Specifically, the first polymerization reaction is used to form a stable three-dimensional network structure in the intermediate layer. The reaction conditions within the aforementioned limited range allow the polymer matrix A to fully cross-link and polymerize, forming a uniform and stable three-dimensional cross-linked network. This better and more uniformly fixes the fast ion conductor within it, further ensuring the smoothness of the ion permeation pathway in the intermediate layer. Simultaneously, it endows the composite electrolyte with superior uniformity and self-supporting properties, working synergistically with the fast ion conductor to further improve the ionic conductivity of the intermediate layer, laying the foundation for the excellent performance of the secondary battery.
[0101] For example, the conditions for the first polymerization reaction are ultraviolet irradiation for 0.5h, 0.7h, 0.9h, 1.1h, 1.3h, 1.5h, 1.7h, 1.9h or 2h, or a range of any two of these values.
[0102] When the conditions for the first polymerization reaction are heating, the heating temperature is, for example, 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C, or 70°C, or a range of any two of these values; the heating time is, for example, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, or 4h, or a range of any two of these values.
[0103] In one specific embodiment, the conditions for the second polymerization reaction are ultraviolet irradiation for 0.5-2 hours or heating at 50-70°C for 1-4 hours. The second polymerization reaction is used to form the first and second surface layers. The same defined reaction conditions allow the polymer matrix B to fully polymerize, ensuring good surface layer forming quality and further enhancing the structural stability of the surface layer. This facilitates the uniform dispersion of the inorganic electrolyte within the surface layer, fully leveraging the role of the inorganic electrolyte in enhancing the mechanical strength and ionic conductivity of the composite electrolyte. Simultaneously, suitable polymerization conditions allow the polymer matrix B to retain good flexibility, better buffering the volume deformation during electrode charging and discharging, further improving the interfacial compatibility between the composite electrolyte and the electrode, and ensuring smooth ion transport between the surface layer and the electrode. Furthermore, the mild and easily controllable polymerization reaction conditions further improve the preparation efficiency and batch uniformity of the composite electrolyte, making it more conducive to large-scale production. It also avoids problems such as component agglomeration and structural defects caused by improper reaction conditions, better ensuring the comprehensive performance of the composite electrolyte, and thus synergistically improving the cycle performance and rate performance of the secondary battery.
[0104] For example, the conditions for the second polymerization reaction are ultraviolet irradiation for 0.5h, 0.7h, 0.9h, 1.1h, 1.3h, 1.5h, 1.7h, 1.9h or 2h, or a range of any two of these values.
[0105] When the conditions for the second polymerization reaction are heating, the heating temperature is, for example, 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C, or 70°C, or a range of any two of these values; the heating time is, for example, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, or 4h, or a range of any two of these values.
[0106] A third aspect of the present invention provides a secondary battery comprising the composite electrolyte described in the first aspect, or the composite electrolyte prepared by the method described in the second aspect. This secondary battery exhibits excellent thermal safety, cycle performance, and rate performance.
[0107] A fourth aspect of the present invention provides a method for preparing a secondary battery, comprising the following steps:
[0108] A secondary battery is obtained by placing a positive electrode and a negative electrode on both sides of the composite electrolyte; or,
[0109] A first polymerization reaction is carried out on a first mixture comprising a monomer of polymer matrix A, a fast ion conductor, lithium salt A, and initiator A to obtain an intermediate layer;
[0110] A second mixture comprising a monomer of polymer matrix B, an inorganic electrolyte, lithium salt B, and initiator B is coated onto the first and second surfaces of an intermediate layer, respectively. A positive electrode is then placed on the side of the second mixture away from the first surface, and a negative electrode is placed on the side of the second mixture away from the second surface. A second polymerization reaction is carried out to obtain a secondary battery. The first and second surfaces are arranged opposite to each other.
[0111] In detail, when preparing a secondary battery according to the present invention, a positive electrode and a negative electrode can be respectively disposed on both sides of the composite electrolyte provided by the present invention to obtain a secondary battery. Because this secondary battery uses the aforementioned composite electrolyte, it exhibits excellent thermal safety, cycle performance, and rate performance. The specific reasons have been explained in detail above and will not be repeated here.
[0112] Meanwhile, in the preparation of the secondary battery according to this invention, an intermediate layer can be prepared first, and then positive and negative electrode sheets can be placed in a second mixture for in-situ polymerization (second polymerization reaction). This in-situ polymerization process ensures that the electrolyte slurry (second mixture) fully wets the electrode surface, allowing the composite electrolyte to form a tight contact with the electrode surface, improving the bonding force at the electrode-composite electrolyte interface, reducing interfacial impedance, and significantly improving the cycle stability and thermal safety of the secondary battery. In addition, the decomposition products of the initiator during the polymerization reaction can further modify the electrode surface, reduce interfacial polarization, and improve the active ion transport efficiency, further enhancing the rate performance of the secondary battery.
[0113] It is conceivable that, in addition to the aforementioned composite electrolyte, the secondary battery of the present invention also includes a positive electrode and a negative electrode.
[0114] The present invention does not specifically limit the structure of the positive electrode sheet. In one embodiment, the positive electrode sheet includes a positive current collector and a positive active layer disposed on at least a portion of the surface of the positive current collector. The positive active layer includes the aforementioned positive active material, conductive agent and binder.
[0115] This invention does not specifically limit the material of the positive electrode current collector; it can be any material conventional in the art. For example, the material of the positive electrode current collector can be either aluminum foil or nickel foil.
[0116] This invention does not specifically limit the type of conductive agent; it can be any material conventional in the art. For example, the conductive agent can be selected from at least one of carbon black, acetylene black, graphene, Ketjen black, and carbon fiber.
[0117] This invention does not specifically limit the type of adhesive, which can be a conventional material in the art. For example, the adhesive can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, and polyurethane.
[0118] This invention does not specifically limit the preparation method of the positive electrode sheet. In one embodiment, the positive electrode sheet can be prepared by a method including the following steps:
[0119] The positive electrode active material of the present invention is dispersed with a conductive agent and a binder in an N-methylpyrrolidone (NMP) solvent and thoroughly stirred to form a uniform positive electrode slurry. The positive electrode slurry is then uniformly coated onto a positive electrode current collector, and after drying, rolling and slitting, a positive electrode sheet is obtained.
[0120] This invention does not impose specific limits on the amount of positive electrode active material, conductive agent and binder, and can be adjusted according to the actual situation.
[0121] The present invention does not specifically limit the structure of the negative electrode sheet. In one embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least a portion of the surface of the negative electrode current collector. The negative electrode active layer includes a negative electrode active material, a binder, and a conductive agent.
[0122] This invention does not specifically limit the material of the negative electrode current collector; it can be any conventional material in the art. For example, the negative electrode current collector can be any of copper foil, nickel foam, or copper foam.
[0123] This invention does not specifically limit the type of negative electrode active material, and it can be any negative electrode active material commonly used in batteries. For example, the negative electrode active material can be selected from at least one of graphite, hard carbon, soft carbon, mesophase carbon microspheres, silicon-based negative electrode materials (mainly including silicon suboxide and silicon-carbon negative electrodes), tin-based negative electrode materials (mainly including tin and tin alloys).
[0124] This invention does not specifically limit the type of binder; it can be any binder commonly used in battery negative electrodes. For example, the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.
[0125] This invention does not specifically limit the type of conductive agent; it can be any conductive agent commonly used in the negative electrode of batteries. For example, the conductive agent can be selected from at least one of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, and graphene.
[0126] This invention does not specifically limit the preparation method of the negative electrode sheet. In one embodiment, the negative electrode sheet can be prepared by a method including the following steps:
[0127] The negative electrode active material, conductive agent, and binder are dispersed in deionized water and thoroughly stirred to form a uniform negative electrode slurry. The negative electrode slurry is then uniformly coated onto the negative electrode current collector, and after drying, rolling, and slitting, a negative electrode sheet is obtained.
[0128] This invention does not impose specific limits on the amount of negative electrode active material, conductive agent, and binder, and these amounts can be adjusted according to actual conditions.
[0129] A fifth aspect of the present invention provides a battery pack comprising the aforementioned secondary battery. This battery pack exhibits excellent thermal safety, cycle performance, and rate performance.
[0130] The battery pack of the present invention may include two or more batteries, and the specific number can be selected by those skilled in the art according to actual needs.
[0131] It should be noted that the individual cells that make up the battery pack can be electrically connected by conventional methods in the art, such as series connection, parallel connection, or a hybrid connection that includes both of these connection methods, and there are no particular limitations on this.
[0132] A sixth aspect of the present invention provides an electrical device including the aforementioned battery pack. Thanks to the high ionic conductivity, excellent interfacial compatibility, and thermal stability of the composite electrolyte used in the battery pack, the electrical device exhibits significantly improved cycle life and thermal safety performance while possessing high-rate charge / discharge capabilities.
[0133] The electrical equipment provided by this invention can be conventional electrical equipment in the field, such as power equipment (e.g., electric vehicles, electric cars), electrical equipment (e.g., mobile phones, tablets, laptops, digital cameras, etc.), wearable devices (e.g., watches, bracelets, VR glasses, etc.), energy storage power stations, etc., and there are no particular limitations on them.
[0134] The technical solution of the present invention will be further described below with reference to specific embodiments.
[0135] Example 1
[0136] The preparation method of the composite electrolyzer in this embodiment includes the following steps:
[0137] 1) Mix the monomers ethyl acrylate, fast ion conductor succinate, and lithium salt A (lithium bis(trifluoromethanesulfonyl)imide) of polymer matrix A, and stir at 25°C for 0.5 h. Add crosslinking agent A (polyethylene glycol diacrylate) at 1 wt% of the monomers of polymer matrix A, and initiator A (diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide). Continue stirring for 15 min to obtain an intermediate layer electrolyte slurry (first mixture). The mass ratio of monomers of polymer matrix A, fast ion conductor, lithium salt A, and initiator A is 50:50:28.7:1. Inject the intermediate layer electrolyte slurry into a polytetrafluoroethylene mold and irradiate with 365 nm ultraviolet light for 1 h to carry out the first polymerization reaction, obtaining the intermediate layer.
[0138] 2) Mix the monomer ethyl acrylate of polymer matrix B, inorganic electrolyte LLZTO powder, and lithium salt B lithium bis(trifluoromethanesulfonyl)imide, and stir at room temperature for 0.5 h. Add crosslinking agent B polyethylene glycol diacrylate at 1 wt% of the monomer of polymer matrix B, and initiator B azobisisobutyronitrile, and continue stirring for 15 min to obtain a surface layer electrolyte slurry (second mixture). The mass ratio of monomer of polymer matrix B, inorganic electrolyte, lithium salt B, and initiator B is 100:30:28.7:2. Uniformly coat the surface layer electrolyte slurry onto both sides of the intermediate layer (first surface and second surface). After heating at 70°C for 2 h for the second polymerization reaction, bake at 55°C for 8 h to obtain a composite electrolyte (including the intermediate layer, and the first and second surface layers located on both sides of the intermediate layer).
[0139] The method for preparing the secondary battery in this embodiment includes the following steps:
[0140] A first polymerization reaction is carried out on a first mixture comprising a monomer of polymer matrix A, a fast ion conductor, lithium salt A, crosslinking agent A and initiator A to obtain an intermediate layer;
[0141] A second mixture comprising a monomer of polymer matrix B, an inorganic electrolyte, lithium salt B, a crosslinking agent B, and an initiator B is coated onto the first and second surfaces of an intermediate layer, respectively. A positive electrode is then placed on the side of the second mixture away from the first surface, and a negative electrode is placed on the side of the second mixture away from the second surface. A second polymerization reaction is carried out to obtain a secondary battery. The first and second surfaces are arranged opposite to each other.
[0142] The types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the preparation method of composite electrolysis in this embodiment.
[0143] Example 2
[0144] The preparation method of the composite electrolyzer in this embodiment includes the following steps:
[0145] 1) The monomers of polymer matrix A, butyl acrylate, fast ion conductor liquid 1-n-butyl-1-methylpyrrolidine di(trifluoromethylsulfonyl)imide, and lithium salt A, lithium bisfluorosulfonylimide, are mixed and stirred at 25°C for 0.5 h. Crosslinking agent A, polyethylene glycol diacrylate, is added at an amount of 1 wt% of the monomers of polymer matrix A, and initiator A, diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, and stirring is continued for 15 min to obtain an intermediate layer electrolyte slurry (first mixture); wherein, the mass ratio of monomers of polymer matrix A, fast ion conductor, lithium salt A, and initiator A is 70:30:18.7:1.2. The intermediate layer electrolyte slurry is injected into a polytetrafluoroethylene mold and irradiated with 365 nm ultraviolet light for 0.5 h to carry out the first polymerization reaction to obtain the intermediate layer.
[0146] 2) Polymer matrix B (butyl acrylate), inorganic electrolyte lithium lanthanum zirconium oxide (LLZO) powder, and lithium salt B (lithium bis(fluorosulfonyl)imide) are mixed and stirred at room temperature for 0.5 h. Crosslinking agent polyethylene glycol diacrylate is added at a ratio of 1 wt% to the monomer of polymer matrix B, and initiator B (azobisisobutyronitrile) is added. Stirring continues for 15 min to obtain a surface layer electrolyte slurry. The mass ratio of polymer matrix B monomer, inorganic electrolyte, lithium salt B, and initiator B is 100:10:18.7:2. The surface layer electrolyte slurry is uniformly coated onto both sides of the intermediate layer. After a second polymerization reaction at 50°C for 4 h, the mixture is dried at 55°C for 8 h to obtain a composite electrolyte (including the intermediate layer, and a first and second surface layer located on both sides of the intermediate layer).
[0147] The method for preparing the secondary battery in this embodiment includes the following steps:
[0148] A first polymerization reaction is carried out on a first mixture comprising a monomer of polymer matrix A, a fast ion conductor, lithium salt A, crosslinking agent A and initiator A to obtain an intermediate layer;
[0149] A second mixture comprising a monomer of polymer matrix B, an inorganic electrolyte, lithium salt B, a crosslinking agent B, and an initiator B is coated onto the first and second surfaces of an intermediate layer, respectively. A positive electrode is then placed on the side of the second mixture away from the first surface, and a negative electrode is placed on the side of the second mixture away from the second surface. A second polymerization reaction is carried out to obtain a secondary battery. The first and second surfaces are arranged opposite to each other.
[0150] In this embodiment, the types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the preparation method of composite electrolysis in this embodiment when preparing the secondary battery.
[0151] Example 3
[0152] The preparation method of the composite electrolyzer in this embodiment includes the following steps:
[0153] 1) Mix ethyl methacrylate (monomer of polymer matrix A), 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide (fast ion conductor), and lithium salt A (lithium difluorooxalatoborate). Stir at 25°C for 0.5 h. Add crosslinking agent A (polyethylene glycol diacrylate) at 1 wt% of the monomer of polymer matrix A, and initiator A (diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide). Continue stirring for 15 min to obtain an intermediate layer electrolyte slurry (first mixture). The mass ratio of monomer of polymer matrix A, fast ion conductor, lithium salt A, and initiator A is 30:70:14.3:0.04. Inject the intermediate layer electrolyte slurry into a polytetrafluoroethylene mold and irradiate with 365 nm ultraviolet light for 1 h to carry out the first polymerization reaction, obtaining the intermediate layer.
[0154] 2) Ethyl methacrylate monomer of polymer matrix B, lithium lanthanum titanium oxide (LLTO) powder of inorganic electrolyte, and lithium salt B lithium difluorooxalate borate were mixed and stirred at room temperature for 0.5 h. Polyethylene glycol diacrylate crosslinking agent was added at 1 wt% of the monomer of polymer matrix B, and azobisisobutyronitrile (ANOVA) initiator was added. Stirring continued for 15 min to obtain a surface layer electrolyte slurry. The mass ratio of monomer of polymer matrix B, inorganic electrolyte, lithium salt B, and initiator B was 100:50:14.3:2. The surface layer electrolyte slurry was uniformly coated on both sides of the intermediate layer. After heating at 60 °C for 3 h for a second polymerization reaction, it was dried at 55 °C for 8 h to obtain a composite electrolyte (including the intermediate layer, and a first and second surface layer located on both sides of the intermediate layer).
[0155] The method for preparing the secondary battery in this embodiment includes the following steps:
[0156] A first polymerization reaction is carried out on a first mixture including a monomer of polymer matrix A, a fast ion conductor, lithium salt A, initiator A, and crosslinking agent A to obtain an intermediate layer;
[0157] A second mixture comprising a monomer of polymer matrix B, an inorganic electrolyte, lithium salt B, a crosslinking agent B, and an initiator B is coated onto the first and second surfaces of an intermediate layer, respectively. A positive electrode is then placed on the side of the second mixture away from the first surface, and a negative electrode is placed on the side of the second mixture away from the second surface. A second polymerization reaction is carried out to obtain a secondary battery. The first and second surfaces are arranged opposite to each other.
[0158] In this embodiment, the types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the preparation method of composite electrolysis in this embodiment when preparing the secondary battery.
[0159] Example 4
[0160] This embodiment is basically the same as Embodiment 1, except that:
[0161] In step 1), the conditions for the first polymerization reaction are heating at 50°C for 4 hours;
[0162] In step 2), the conditions for the second polymerization reaction are ultraviolet light irradiation for 0.5 h.
[0163] In this embodiment, the types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the composite electrolysis preparation method of this embodiment. The difference lies in the following: after coating the surface layer, a second polymerization reaction is carried out to obtain a composite electrolyte. A positive electrode and a negative electrode are respectively placed on both sides of the composite electrolyte to obtain a secondary battery.
[0164] Example 5
[0165] This embodiment is basically the same as Embodiment 1, except that:
[0166] In step 1), the conditions for the first polymerization reaction are heating at 60°C for 3 hours;
[0167] In step 2), the condition for the second polymerization reaction is irradiation with ultraviolet light for 1 hour.
[0168] In this embodiment, the types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the composite electrolysis preparation method of this embodiment. The difference lies in the following: after coating the surface layer, a second polymerization reaction is carried out to obtain a composite electrolyte. A positive electrode and a negative electrode are respectively placed on both sides of the composite electrolyte to obtain a secondary battery.
[0169] Example 6
[0170] This embodiment is basically the same as Embodiment 1, except that:
[0171] In step 1), the conditions for the first polymerization reaction are heating at 70°C for 1 hour;
[0172] In step 2), the condition for the second polymerization reaction is irradiation with ultraviolet light for 2 hours.
[0173] In this embodiment, the types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the composite electrolysis preparation method of this embodiment. The difference lies in the following: after coating the surface layer, a second polymerization reaction is carried out to obtain a composite electrolyte. A positive electrode and a negative electrode are respectively placed on both sides of the composite electrolyte to obtain a secondary battery.
[0174] Example 7
[0175] This embodiment is basically the same as Embodiment 1, except that:
[0176] In step 1), the conditions for the first polymerization reaction are heating at 70°C for 1 hour;
[0177] In step 2), the conditions for the second polymerization reaction are heating at 70°C for 1 hour.
[0178] In this embodiment, the types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the preparation method of composite electrolysis in this embodiment when preparing the secondary battery.
[0179] Example 8
[0180] This embodiment is basically the same as Embodiment 1, except that:
[0181] In 1), the mass ratio of monomer, fast ion conductor, lithium salt A and initiator A in polymer matrix A is 80:20:28.7:1.8.
[0182] In this embodiment, the types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the preparation method of composite electrolysis in this embodiment when preparing the secondary battery.
[0183] Example 9
[0184] This embodiment is basically the same as Embodiment 1, except that:
[0185] 2) The mass ratio of monomer, inorganic electrolyte, lithium salt B and initiator B in polymer matrix B is 100:60:28.7:2.
[0186] In this embodiment, the types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the preparation method of composite electrolysis in this embodiment when preparing the secondary battery.
[0187] Example 10
[0188] This embodiment is basically the same as Embodiment 1, except that:
[0189] The thickness of the intermediate layer is changed. After the second mixture is applied to one surface of the intermediate layer, a second polymerization reaction is carried out. If the thickness of the first surface layer does not reach the target thickness after the second polymerization reaction, the second mixture needs to be applied again and the second polymerization reaction is carried out until the thickness of the first surface layer reaches the target thickness.
[0190] The prepared composite electrolyte satisfies the following conditions: the thickness of the intermediate layer is 50 μm, the thickness of the first surface layer is 30 μm, and the thickness of the second surface layer is 30 μm.
[0191] In this embodiment, the types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the preparation method of composite electrolysis in this embodiment when preparing the secondary battery.
[0192] Example 11
[0193] This embodiment is basically the same as Embodiment 1, except that:
[0194] The thickness of the intermediate layer remains unchanged. After coating one surface of the intermediate layer with the second mixture, a second polymerization reaction is carried out. If the thickness of the second surface layer does not reach the target thickness after the second polymerization reaction, the second mixture needs to be coated again and the second polymerization reaction is carried out until the thickness of the second surface layer reaches the target thickness.
[0195] The prepared composite electrolyte satisfies the following conditions: the thickness of the intermediate layer is 100 μm, the thickness of the first surface layer is 30 μm, and the thickness of the second surface layer is 30 μm.
[0196] In this embodiment, the types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the preparation method of composite electrolysis in this embodiment when preparing the secondary battery.
[0197] Example 12
[0198] This embodiment is basically the same as Embodiment 1, except that:
[0199] The thickness of the intermediate layer remains unchanged. After coating one surface of the intermediate layer with the second mixture, a second polymerization reaction is carried out. If the thickness of the second surface layer does not reach the target thickness after the second polymerization reaction, the second mixture needs to be coated again and the second polymerization reaction is carried out until the thickness of the second surface layer reaches the target thickness.
[0200] The prepared composite electrolyte satisfies the following conditions: the thickness of the intermediate layer is 100 μm, the thickness of the first surface layer is 20 μm, and the thickness of the second surface layer is 10 μm.
[0201] In this embodiment, the types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the preparation method of composite electrolysis in this embodiment when preparing the secondary battery.
[0202] Example 13
[0203] This embodiment is basically the same as Embodiment 1, except that:
[0204] The thickness of the intermediate layer remains unchanged. After coating one surface of the intermediate layer with the second mixture, a second polymerization reaction is carried out. If the thickness of the second surface layer does not reach the target thickness after the second polymerization reaction, the second mixture needs to be coated again and the second polymerization reaction is carried out until the thickness of the second surface layer reaches the target thickness.
[0205] The prepared composite electrolyte satisfies the following conditions: the thickness of the intermediate layer is 100 μm, the thickness of the first surface layer is 10 μm, and the thickness of the second surface layer is 20 μm.
[0206] In this embodiment, the types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the preparation method of composite electrolysis in this embodiment when preparing the secondary battery.
[0207] Example 14
[0208] This embodiment is basically the same as Embodiment 1, except that:
[0209] The thickness of the intermediate layer is changed. After the second mixture is applied to one surface of the intermediate layer, a second polymerization reaction is carried out. If the thickness of the first surface layer does not reach the target thickness after the second polymerization reaction, the second mixture needs to be applied again and the second polymerization reaction is carried out until the thickness of the first surface layer reaches the target thickness.
[0210] The prepared composite electrolyte satisfies the following conditions: the thickness of the intermediate layer is 100 μm and the thickness of the first surface layer is 50 μm.
[0211] In this embodiment, the types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the preparation method of composite electrolysis in this embodiment when preparing the secondary battery.
[0212] Example 15
[0213] This embodiment is basically the same as Embodiment 1, except that:
[0214] The thickness of the intermediate layer is changed. After the second mixture is applied to one surface of the intermediate layer, a second polymerization reaction is carried out. If the thickness of the second surface layer does not reach the target thickness after the second polymerization reaction, the second mixture needs to be applied again and the second polymerization reaction is carried out until the thickness of the second surface layer reaches the target thickness.
[0215] The prepared composite electrolyte satisfies the following conditions: the thickness of the intermediate layer is 100 μm and the thickness of the second surface layer is 100 μm.
[0216] In this embodiment, the types and proportions of raw materials in the intermediate layer and the types and proportions of raw materials in the second mixture are consistent with those in the preparation method of composite electrolysis in this embodiment when preparing the secondary battery.
[0217] Example 16
[0218] This embodiment is basically the same as Embodiment 1, except that:
[0219] In this embodiment, when preparing the secondary battery, a positive electrode and a negative electrode are respectively disposed on both sides of the composite electrolyte obtained in Example 1 to obtain the secondary battery.
[0220] Example 17
[0221] This embodiment is basically the same as Embodiment 1, except that:
[0222] The thickness of the intermediate layer was changed to make the thickness of the intermediate layer of the composite electrolyte 300μm.
[0223] Example 18
[0224] This embodiment is basically the same as Embodiment 1, except that:
[0225] The thickness of the intermediate layer was changed to make the thickness of the intermediate layer of the composite electrolyte 200μm.
[0226] Comparative Example 1
[0227] This comparative example is basically the same as Example 1, except that:
[0228] The intermediate layer of Example 1 is used as the composite electrolyte in this example.
[0229] In this comparative example, the types and proportions of raw materials in the intermediate layer are consistent with those in the composite electrolysis preparation method of this comparative example when preparing the secondary battery.
[0230] Comparative Example 2
[0231] This comparative example is basically the same as Example 1, except that:
[0232] The composite electrolyte was replaced with an ether-based liquid electrolyte, which consisted of 1,3-dioxolane (DOL) and diethylene glycol dimethyl ether (DME) in a volume ratio of 1:1.
[0233] In this comparative example, the lithium salt used to prepare the secondary battery was 1M lithium bis(trifluoromethanesulfonyl)imide and lithium nitrate with a mass fraction of 2%; the positive electrode active material used was lithium iron phosphate, and the negative electrode was lithium metal.
[0234] Comparative Example 3
[0235] This comparative example is basically the same as Example 1, except that:
[0236] LLZTO is not added to the first and second surface layers.
[0237] In this comparative example, the types and proportions of raw materials in the intermediate layer are consistent with those in the composite electrolysis preparation method of this comparative example when preparing the secondary battery.
[0238] Experimental Example 1
[0239] 1. Some preparation parameters of the composite electrolytes in the examples and comparative examples are shown in Table 1; the thicknesses of the intermediate layer, the first surface layer, and the second surface layer of the composite electrolytes in the examples and comparative examples were tested, and the mechanical strength, ionic conductivity, and ionic conductivity of the intermediate layer of the composite electrolytes in the examples and comparative examples were tested, and the results are shown in Table 2.
[0240] 2. Testing Methods
[0241] 1) Test method for the thickness of the intermediate layer, first surface layer and second surface layer of the composite electrolyte
[0242] Under an inert gas atmosphere, the composite electrolyte to be tested was cut open with a scalpel blade, adhered to the SEM sample stage using conductive adhesive, and vacuum-transferred into the SEM sample chamber. The cross-section of the composite electrolyte was photographed using a scanning electron microscope, and the thickness of each layer was measured. The cross-sectional SEM image of the composite electrolyte in Example 1 is shown below. Figure 1 As shown.
[0243] 2) Test methods for the ionic conductivity of composite electrolytes and the ionic conductivity of the intermediate layer
[0244] Steel sheets were used as blocking electrodes on both sides of the composite electrolyte to be tested, and a button cell was assembled with the composite electrolyte. The AC impedance spectrum of the electrolyte was measured using an electrochemical workstation, with a test frequency of 0.1~10. 6 Hz, ionic conductivity through Calculate, where l is the thickness of the composite electrolyte, R is the AC impedance, and A is the effective contact area between the electrode and the composite electrolyte.
[0245] 3) Test methods for the mechanical strength of composite electrolytes
[0246] The tensile strength of the composite electrolyte under test was tested using a universal testing machine.
[0247] Table 1
[0248]
[0249] Table 2
[0250]
[0251] Experimental Example 2
[0252] 1. Electrochemical performance and cycle performance tests were conducted on the secondary batteries of the examples and comparative examples. The results are shown in Table 3 and... Figure 2 , Figure 3 , Figure 4 , Figure 5 .
[0253] Figure 2 The test method is as follows: the composite electrolyte from Example 1 is assembled into a Li|composite electrolyte|steel sheet battery, and the electrochemical oxidation window of the electrolyte is tested on an electrochemical workstation. For example... Figure 2 As shown, the composite electrolyte of Example 1 has an electrochemical oxidation window of 5.45V and exhibits excellent high-voltage stability.
[0254] Figure 3 The test method is as follows: the composite electrolytes of Example 1, Example 3 and Comparative Example 1 are used to prepare Li|electrolyte|Li symmetric cells, and the test is performed at 0.1 mA / cm². 2 The results of cycle tests, including charging and discharging for 1 hour each, at a given current density. For example... Figure 3 As shown, the Li|Li symmetric cells of Examples 1 and 3 cycle more stably at a lower polarization voltage, demonstrating that the composite electrolytes of Examples 1 and 3 have excellent interfacial compatibility and cycle stability, with the composite electrolyte of Example 1 being the best.
[0255] Figure 4 The test method is as follows: A comparison of the 0.5C charge-discharge cycle test results at 25°C between the Li∣lithium iron phosphate battery assembled with the composite electrolyte prepared in Example 1 and the Li∣lithium iron phosphate liquid battery assembled with the ether-based liquid electrolyte in Comparative Example 2. (See the graph.) Figure 4 As shown, the cycle stability of the battery prepared in Example 1 is better than that of Comparative Example 2.
[0256] Figure 5 The test method is as follows: A comparison chart of the 1C charge-discharge cycle test results of the Li∣lithium iron phosphate batteries assembled in Example 1 and Comparative Example 3 at 25°C is shown. Figure 5 As shown, after 800 cycles, the capacity retention rate of the battery in Example 1 was 83%, while the capacity retention rate of the battery in Comparative Example 3 was 67% after 400 cycles, demonstrating that the composite electrolyte containing inorganic electrolyte can improve battery cycle performance.
[0257] 2. Testing Methods
[0258] 1) Test method for full battery cycle performance
[0259] A Li∣electrolyte∣lithium iron phosphate battery was prepared. Using a battery charge-discharge tester, the battery was charged and discharged at 25°C. The charge-discharge regime was as follows: For the first two cycles, the battery was charged at a constant current of 0.1C to 4.2V, then charged at a constant voltage of 4.2V until the current decreased to 0.05C, and then discharged at a constant current of 0.1C to 2.5V to activate the battery. From the third cycle onwards, the battery was charged at a constant current of 0.5C to 4.2V, then charged at a constant voltage of 4.2V until the current decreased to 0.05C, and then discharged at a constant current of 0.5C to 2.5V. After resting for 5 minutes, the next charge-discharge cycle was performed, and the charge-discharge data were recorded. The capacity retention rate of the Nth cycle can be calculated using the following formula:
[0260] Capacity retention rate = discharge specific capacity of the Nth cycle / discharge specific capacity of the 3rd cycle × 100%.
[0261] Table 3
[0262]
[0263] As shown in Tables 2 and 3, compared with the comparative example, the secondary battery prepared by the composite electrolyte of the present invention has a longer cycle life and better rate performance, which proves that the composite electrolyte provided by the present invention can give full play to the synergistic effect of each component, thereby better improving the cycle performance and rate performance of the secondary battery.
[0264] The above embodiments are merely preferred embodiments provided to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention.
Claims
1. A composite electrolyte, characterized in that, It includes a first surface layer, an intermediate layer and a second surface layer stacked in sequence. The intermediate layer includes a polymer matrix A, a fast ion conductor and a lithium salt A. The first surface layer and the second surface layer each independently include a polymer matrix B, an inorganic electrolyte and a lithium salt B.
2. The composite electrolyte according to claim 1, characterized in that, The polymer matrix A and the polymer matrix B each independently include at least one of poly(meth)acrylic acid, poly(meth)acrylate, polycarbonate, polyacetate, polyolefin, and polyether-modified (meth)acrylate.
3. The composite electrolyte according to claim 2, characterized in that, The poly(meth)acrylic acid includes at least one of polyacrylic acid and polymethacrylic acid; and / or, the poly(meth)acrylate includes at least one of polyacrylate, polymethyl methacrylate, polyethyl methacrylate, and polydiacrylate; and / or, the polycarbonate includes at least one of polypropylene carbonate, polyvinyl carbonate, and polyvinyl carbonate; and / or, the polyacetate includes polyvinyl acetate; and / or, the polyolefin includes polystyrene; and / or, the polyether-modified (meth)acrylate includes at least one of polyethylene glycol dimethacrylate, polyethylene glycol methacrylate, polyethylene glycol methyl ether methacrylate, and polyethylene glycol dimethyl ether.
4. The composite electrolyte according to claim 1, characterized in that, The ratio of the thickness of the first surface layer to the thickness of the intermediate layer is (1-3):(10-30); and / or, the ratio of the thickness of the second surface layer to the thickness of the intermediate layer is (1-3):(10-30).
5. The composite electrolyte according to claim 4, characterized in that, The thickness of the intermediate layer is 100-300 μm; and / or, the thickness of the first surface layer is 10-30 μm; and / or, the thickness of the second surface layer is 10-30 μm.
6. The composite electrolyte according to claim 1, characterized in that, In the first surface layer, the mass ratio of the polymer matrix B, the inorganic electrolyte, and the lithium salt B is (50-100):(10-50):(10-60); and / or, in the intermediate layer, the mass ratio of the polymer matrix A, the fast ion conductor, and the lithium salt A is (30-70):(30-70):(10-60); and / or, in the second surface layer, the mass ratio of the polymer matrix B, the inorganic electrolyte, and the lithium salt B is (50-100):(10-50):(10-60).
7. The composite electrolyte according to claim 1, characterized in that, The inorganic electrolyte includes at least one of lithium lanthanum zirconium oxide, lithium lanthanum titanium oxide, lithium lanthanum zirconium tantalum oxide, lithium titanium aluminum phosphate, and lithium aluminum germanium phosphate; and / or, lithium salt A and lithium salt B each independently include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium difluorooxalate borate; and / or, the fast ion conductor includes at least one of ionic liquid and succinate.
8. A method for preparing the composite electrolyte according to any one of claims 1-7, characterized in that, Includes the following steps: 1) A first mixture comprising monomers of polymer matrix A, fast ion conductor, lithium salt A, crosslinking agent A and initiator A is subjected to a first polymerization reaction to obtain an intermediate layer; 2) A second mixture comprising a monomer of polymer matrix B, an inorganic electrolyte, lithium salt B, a crosslinking agent B, and an initiator B is coated onto the first and second surfaces of the intermediate layer, respectively, and a second polymerization reaction is carried out to obtain the composite electrolyte; the first and second surfaces are arranged opposite to each other.
9. The preparation method according to claim 8, characterized in that, The conditions for the first polymerization reaction are ultraviolet irradiation for 0.5-2 hours or heating at 50-70°C for 1-4 hours; and / or, the conditions for the second polymerization reaction are ultraviolet irradiation for 0.5-2 hours or heating at 50-70°C for 1-4 hours.
10. A secondary battery, characterized in that, Includes the composite electrolyte as described in any one of claims 1-7, or the composite electrolyte prepared by the preparation method described in claim 8 or 9.
11. A method for preparing a secondary battery according to claim 10, characterized in that, Includes the following steps: A positive electrode and a negative electrode are respectively disposed on both sides of the composite electrolyte to obtain the secondary battery; or, A first polymerization reaction is carried out on a first mixture comprising a monomer of polymer matrix A, a fast ion conductor, lithium salt A, and initiator A to obtain an intermediate layer; A second mixture comprising a monomer of polymer matrix B, an inorganic electrolyte, lithium salt B, and initiator B is coated onto the first and second surfaces of the intermediate layer, respectively. Subsequently, a positive electrode is disposed on the side of the second mixture away from the first surface, and a negative electrode is disposed on the side of the second mixture away from the second surface. A second polymerization reaction is carried out to obtain the secondary battery. The first and second surfaces are arranged opposite to each other.
12. A battery pack, characterized in that, This includes the secondary battery as described in claim 10, or the secondary battery prepared by the preparation method described in claim 11.
13. An electrical appliance, characterized in that, Includes the battery pack as described in claim 12.